Self efficacy: psychoeducation program on facing the computer-based national exam - Nugraha, Dwi Yan; Fitri, Alfira Sandika; Harits, Ajeng Octavia Insani; Nurzakinah. A, Salsabilla; Yusuf, A. Muh.; Fikran, Andi Muhammad; Qadri, Andi Ramdan Al (International research journal of management, IT and social sciences, 2020)
The emergence of anxiety on students facing the national exam is caused by the lack of self-efficacy. The low self-efficacy of students has an impact on the psychological state that can create feelings of fear and pressure on students, thus hampering students' success in facing the national exam. This study wants to see an increase in students' self-efficacy through psychoeducation programs. The design in this study uses The One Group Pre-Post Test Design. The number of participants in this study was 100 participants, obtained using a purposive sampling technique. Data were collected using a self-efficacy scale consisting of 11 items. The statistical test used is Wilcoxon with SOFA software version 1.5.2. The results of this study indicate that the pretest score obtained M = 25.0 and the post-test score obtained M = 31.0. The results of testing the hypothesis obtained values ??W (486.5) and p (.000 < 0.05), so there is an increase in self-efficacy through psychoeducation programs. The difference in the pretest and posttest scores shows that the psychoeducation program is an activity that can improve students' self-efficacy, especially for students of 4 senior high school Bone which will face the national exam.